Phase permeability improver, fracturing fluid system containing phase permeability improver, and preparation methods and applications of phase permeability improver and fracturing fluid system
By using phase permeability improvement agents prepared by copolymers such as acrylamide, a strong adsorption fracturing fluid system is formed, which solves the problems of water control and oil production decline in traditional fracturing development, and achieves efficient, stable, water control and good long-term effects.
Patent Information
- Application Number
- CN202311067223.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-23
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2043-08-23
AI Technical Summary
In traditional hydraulic fracturing development, low-permeability oil reservoirs have problems such as difficult water control and rapid water rise after fracturing. Conventional chemical water blocking technology will block the oil flow channel, resulting in a decrease in oil production.
The phase penetration improver obtained by hydrolysis of acrylamide, 2-acrylamide-2-methylpropanesulfonic acid, cationic hydrophobic monomers A and B is used to form a fracturing liquid system with strong adsorption ability to ensure that the adsorption capacity on the rock pore surface is strong, the concentration is low, and the oil stabilization and water control function is maintained before and after the glue is broken.
It significantly reduces the water-phase permeability after fracturing construction, and has little impact on the oil-phase permeability, has obvious effects on oil-stabilizing and water-controlled effects, and has good long-term effectiveness, which significantly improves the stable production effect of fracturing construction in low-permeability reservoirs.
Smart Images

Figure BDA0004409887520000071 
Figure BDA0004409887520000121 
Figure BDA0004409887520000131
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of oil and gas field development, and relates to a phase permeability improver, a fracturing fluid system containing the same, and respective preparation methods and applications. Background Art
[0002] Low permeability oil fields have large seepage resistance and low oil well development efficiency. Hydraulic fracturing is usually used to improve development efficiency. However, for low permeability reservoirs with high degree of fracture development and complex oil-water relationship, the traditional hydraulic fracturing development method has poor effect. After fracturing construction, the water content rises quickly and the oil production decreases, resulting in a sharp increase in the cost of ground crude oil dehydration and water treatment, affecting the normal production of the oil field. In order to further improve the fracturing development efficiency of low permeability reservoirs, it is necessary to carry out research on stable oil and water control fracturing technology. In the research on stable oil and water control technology and stable oil and water control fracturing technology for low permeability reservoirs, conventional chemical water plugging technology will block the oil flow channel while blocking the formation water channel, causing a significant decrease in oil production. The relative permeability improver (phase permeability improver) reduces the water phase permeability to a greater extent than the oil phase permeability, has the characteristics of controlling water without blocking oil, and has broad application prospects. Therefore, the fracturing fluid system based on relative permeability improver is also a hot spot and main direction of research.
[0003] The phase permeability improver fracturing fluid system is composed of a phase permeability improver and traditional fracturing fluid. The core component of the system is the phase permeability improver. The structure and performance of the phase permeability improver and its compatibility with the fracturing fluid system directly affect the performance and effect of the phase permeability improver fracturing fluid system.
[0004] Chinese invention patent application CN1614193A discloses a fracturing method for improving oil recovery by using a phase permeability improver, wherein the phase permeability improver includes polyacrylamide and a cross-linking agent, wherein the molecular weight of the polyacrylamide is 1-40 million, and the cross-linking agent is one or more of organic chromium, inorganic chromium, organic aluminum, and inorganic aluminum; Chinese invention patent CN113666686B discloses a method for preparing a selective water plugging system, which is composed of cement, a modifier, a pore-forming agent, an admixture, a co-solvent, etc., has strong oil stabilization and water control properties, can effectively reduce the water phase permeability, and has little effect on the oil phase permeability; however, the cross-linking system and cement used in the above oil stabilization and water control technologies have certain damage to low permeability reservoirs.
[0005] Chinese invention patent CN111574992B discloses a nano-phase permeability improver for acid fracturing and its preparation method, which is prepared by grafting polyacrylamide molecular chains on the surface of nano-silica particles through a silane coupling agent, and then cationizing the grafted polyacrylamide molecular chains. It has good acid resistance and the water phase permeability is reduced by more than 60%; Luo Shuai studied a nano-phase permeability improver for low permeability carbonate reservoirs in his "Research on the Limits of Application Technology for Preparation and Application of Phase Permeability Improved Fracturing Fluids in Carbonate Reservoirs" in his 2020 engineering master's degree thesis at China University of Petroleum. Fracturing fluid, firstly adopts coupling grafting method to modify the surface of silica, and on this basis, prepares cationized KH570-SiO2-PAM phase permeability improver, the particle size is about 150nm, can reduce the water phase permeability by more than 70%, further introduces surfactant and temperature stabilizer etc. to form phase permeability improver fracturing fluid system, has obvious water control effect, among which the water phase permeability is reduced by about 70%, and the oil phase permeability is reduced by about 13%; however, the process of nano phase permeability improver prepared by this method is cumbersome and complicated, and the product cost is high, which is not conducive to industrial promotion and application.
[0006] Chinese invention patent CN102093880B discloses an oil well water control agent and its preparation method, which is a terpolymer of AM / AMPS / non-ionic hydrophobic monomer prepared by inverse emulsion polymerization. When the injection concentration is 0.12%, the water phase permeability reduction rate is 72.80-90.53%, and the oil phase permeability reduction rate is 7.71-17.76%. The water control agent is used at a relatively high concentration; Gong Jun et al. studied a phase permeability improvement drag reducer emulsion in "Preparation and Field Application of a Phase Permeability Improved Drag Reducer Emulsion", Fault Block Oil and Gas Field, 2020, 27(04), which is polymerized from acrylamide, 2-acrylamido-2-methylpropanesulfonic acid and N,N-dimethylacrylamide. The drag reduction rate of the system can reach 72.5%, which can reduce the water phase permeability by more than 80% and the oil phase permeability reduction rate by about 15%. The above-mentioned phase permeability improver is synthesized using non-ionic monomers, and has a weak adsorption capacity for cores. Moreover, when used as a fracturing fluid system, its water control performance and long-term effectiveness after gel breaking have not been studied, which is not conducive to understanding the effective period of fracturing water control.
[0007] In view of the shortcomings of the above-mentioned phase permeability improvers and phase permeability improver fracturing fluid systems, it is necessary to invent a fracturing fluid system with strong adsorption ability on the rock pore surface, simple preparation process, low usage concentration, and oil stabilization and water control functions before and after gel breaking. Summary of the invention
[0008] The present invention aims at low-permeability oil reservoirs with a high degree of fracture development and complex oil-water relationship. When using traditional fracturing construction, there are problems such as great difficulty in water control and rapid increase of water content after fracturing. The present invention provides a phase permeability improver, a fracturing fluid system containing the same, and their respective preparation methods and applications. The fracturing fluid system can significantly reduce the permeability of the water phase after fracturing construction, while having little effect on the permeability of the oil phase, having obvious oil stabilization and water control effects, and having good long-term effectiveness, and can significantly improve the stable production effect of fracturing construction in low-permeability oil reservoirs.
[0009] One of the technical solutions of the present invention is:
[0010] Provided is a phase penetration improver, which is obtained by copolymerizing acrylamide AM, a functional monomer 2-acrylamide-2-methylpropanesulfonic acid AMPS, a cationic hydrophobic monomer A and a cationic hydrophobic monomer B and then hydrolyzing them. Taking acrylamide AM as a reference, the amounts of the raw materials are: 10-20 wt.% of the functional monomer 2-acrylamide-2-methylpropanesulfonic acid AMPS, 5-10 wt.% of the cationic hydrophobic monomer A and 1-3 wt.% of the cationic hydrophobic monomer B.
[0011] The cationic hydrophobic monomer A is at least one of tetradecyl dimethyl allyl ammonium chloride, hexadecyl dimethyl allyl ammonium chloride and octadecyl dimethyl allyl ammonium chloride, preferably octadecyl dimethyl allyl ammonium chloride.
[0012] The cationic hydrophobic monomer B is at least one of methacryloyloxyethyl trimethyl ammonium chloride, acryloyloxyethyl trimethyl ammonium chloride and acryloyloxyethyl dimethyl benzyl ammonium chloride; preferably methacryloyloxyethyl trimethyl ammonium chloride.
[0013] The particle size of the phase penetration improver is 100-120 meshes, and the viscosity average molecular weight is 500,000-5,000,000.
[0014] The mechanism of action of the phase penetration improver of the present invention is:
[0015] ① Cationic hydrophobic monomers A and B make the phase permeability improver have strong adsorption capacity on the rock surface, which is a necessary condition for successful water control;
[0016] ② The cationic hydrophobic monomer A used is a highly efficient associative monomer. When the concentration of the prepared phase permeability improver is higher than a certain critical concentration CAC, the macromolecular chains aggregate through hydrophobic association to form supramolecular aggregates mainly based on intermolecular association. The network structure of the solution is more compact, and the binding capacity of water molecules is enhanced, so that the water control performance of the phase permeability improver is further increased; at the same time, the intermolecular association enhances the temperature and salt resistance of the phase permeability improver, which is conducive to reducing the use concentration; due to the presence of the cationic hydrophobic monomer, the solution can still form supramolecular aggregates mainly based on intermolecular association after breaking the gel, which fully guarantees the water control performance of the phase permeability improver after breaking the gel;
[0017] ③ The introduction of the temperature-resistant and salt-resistant functional monomer 2-acrylamide-2-methylpropanesulfonic acid AMPS can promote the association of the cationic hydrophobic monomer A in the phase penetration improver, making the supramolecular aggregate structure of the solution stronger. The introduction of 2-acrylamide-2-methylpropanesulfonic acid AMPS makes the polymer have good water solubility and temperature-resistant and salt-resistant properties, which can ensure that the dissolution time of the polymer at room temperature is less than 1.5 minutes, and can be prepared using oilfield wastewater.
[0018] In general, the unique molecular structure of the phase permeability improver of the present invention enables it to have strong adsorption capacity on the surface of rock pores, low usage concentration, and excellent oil stabilization and water control functions before and after gel breaking.
[0019] The second technical solution of the present invention is:
[0020] A method for preparing the above-mentioned phase penetration improver is provided, which specifically comprises the following steps:
[0021] (1) Add acrylamide AM and functional monomer 2-acrylamido-2-methylpropanesulfonic acid AMPS into deionized water and adjust the pH value of the solution to 7.0;
[0022] (2) adding cationic hydrophobic monomer A and cationic hydrophobic monomer B and stirring evenly;
[0023] (3) raising the temperature, adding an initiator, and performing adiabatic polymerization;
[0024] (4) After completion, a hydrolysis agent is added to carry out a hydrolysis reaction;
[0025] (5) Drying to obtain the phase penetration improver.
[0026] The initiator includes an oxidizing agent and a reducing agent.
[0027] The oxidant is at least one of potassium persulfate, ammonium persulfate, sodium persulfate and dibenzoyl peroxide; preferably ammonium persulfate.
[0028] The reducing agent is at least one of sodium formaldehyde sulfoxylate, sodium sulfite, sodium bisulfite and urea, preferably sodium bisulfite.
[0029] That is, the initiator is preferably an ammonium sulfate-sodium bisulfite initiator system.
[0030] Furthermore, the amount of the oxidant is 0.1-0.4 wt.% of acrylamide AM, preferably 0.25 wt.%.
[0031] Furthermore, the amount of the reducing agent is 0.2-0.6 wt.% of acrylamide AM, preferably 0.4 wt.%.
[0032] Furthermore, the hydrolyzing agent is at least one of sodium hydroxide, sodium carbonate and sodium bicarbonate; preferably sodium hydroxide.
[0033] Furthermore, the dosage of the hydrolyzing agent is calculated based on a theoretical hydrolysis degree of 15-35%.
[0034] Furthermore, the polymerization reaction temperature is 30-50° C., and the reaction time is 4-12 hours.
[0035] Preferably, the polymerization reaction temperature is 35-40° C., and the reaction time is 8-12 h.
[0036] Furthermore, the hydrolysis reaction temperature is 80-120° C., and the hydrolysis reaction time is 1-4 h.
[0037] Preferably, the hydrolysis reaction temperature is 90-100° C., and the hydrolysis reaction time is 2-3 h.
[0038] Furthermore, the drying temperature is 80-140° C., and the drying time is 0.5-3 h.
[0039] Preferably, the drying temperature is 100-110° C., and the drying time is 1-2 hours.
[0040] In the technical solution of the present invention, a colloidal product is obtained after adiabatic polymerization, and before the hydrolysis reaction, it is cut into particles with a particle size of 2-4 mm to make the hydrolysis reaction more complete and more efficient; in addition, after the hydrolysis is completed, the dried product needs to be crushed and sieved to obtain the phase penetration improver.
[0041] The third technical solution of the present invention is:
[0042] Provided is a fracturing fluid system, the composition of which includes the above-mentioned phase permeability improver or the phase permeability improver prepared by the above-mentioned preparation method.
[0043] The fracturing fluid composition, by mass percentage, includes: 0.4-1.2% thickener, 0.1-0.5% clay stabilizer, 0.1-0.5% drainage aid, 0.1-0.5% demulsifier, 0.05-0.20% gel breaker, the above-mentioned phase permeability improver or the phase permeability improver prepared by the above-mentioned preparation method.
[0044] The thickener is water-soluble polyacrylamide and its derivatives.
[0045] Furthermore, the thickener is in the form of an emulsion or a powder of 100-120 mesh.
[0046] The clay stabilizer is at least one of potassium chloride, ammonium chloride and quaternary ammonium salt organic clay stabilizers.
[0047] The degassing aid is a fluorocarbon surfactant, including a perfluorodecyl ether fluorocarbon surfactant and / or a perfluorodecyl polyoxyethylene ether fluorocarbon surfactant.
[0048] The demulsifier is a polyether compound, including at least one of polyoxyethylene polyoxypropylene ether demulsifier, polyoxyethylene polyoxypropylene ether demulsifier and polyoxyethylene polyoxypropylene ether demulsifier.
[0049] The breaker is at least one of ammonium persulfate, sodium persulfate, potassium persulfate and capsule breaker.
[0050] The fourth technical solution of the present invention is:
[0051] A preparation method of the above-mentioned fracturing fluid system is provided, and the specific operation is: adding a thickener, a phase permeability improver, a clay stabilizer, a drainage aid, a demulsifier, and a gel breaker into water in sequence, and stirring to obtain the fracturing fluid system.
[0052] Furthermore, the stirring process has a rotation speed of 400-800 rad / min and a stirring time of 1-3 min.
[0053] The fifth technical solution of the present invention is:
[0054] Provided are applications of the phase permeability improver, the phase permeability improver prepared by the preparation method, the fracturing fluid system or the fracturing fluid system prepared by the preparation method in hydraulic fracturing exploitation of oil and gas fields.
[0055] Compared with the prior art, the present invention has the following beneficial effects:
[0056] 1. The phase permeability improver prepared by the present invention has excellent performance due to the unique molecular structure: strong adsorption capacity on the surface of rock pores and low usage concentration; the reduction of water phase permeability is greater than 90%, the reduction of oil phase permeability is less than 10%, and the reduction ratio reaches 10.24, which has good oil stabilization and water control functions; after water injection and flushing of 100PV, the reduction ratio of water phase permeability to oil phase permeability reaches 8.03, which has good long-term effectiveness;
[0057] 2. The phase permeability improver of the present invention has excellent oil stabilization and water control functions before and after gel breaking, and the fracturing fluid system containing the phase permeability improver before and after gel breaking;
[0058] 3. The phase permeability improver and the fracturing fluid system prepared by the present invention have no harm to the ultra-low permeability oil reservoir, the preparation process is simple, easy to industrialize, the product has good water solubility, low use concentration, and good compatibility with conventional fracturing fluid systems;
[0059] 4. The phase permeability improver and its fracturing fluid system can meet the existing fracturing preparation process (online preparation or continuous mixing, etc.), and will not add other additional reagent adding equipment, and has wide adaptability. DETAILED DESCRIPTION
[0060] The following non-limiting examples can enable those skilled in the art to more fully understand the present invention, but do not limit the present invention in any way. The following content is merely an exemplary description of the scope of the present invention, and those skilled in the art can make various changes and modifications to the present invention based on the disclosed content, which should also fall within the scope of the present invention.
[0061] The relevant parameters and technical effects of the present invention are tested according to the following standards:
[0062] 1. The viscosity average molecular weight test of phase permeability improver refers to Section 6.5.3 of SY / T 5862-2020 "Technical Requirements for Polymers for Oil Displacement";
[0063] 2. The evaluation method for the oil stabilization and water control effect of the phase permeability improver or its fracturing fluid system is adjusted based on the reference to Section 7.7 of SY / T5107-2016 "Evaluation Method for Performance of Water-Based Fracturing Fluids"; the specific experimental steps are as follows:
[0064] (1) Inject simulated brine into the core at a constant flow rate to fully saturate the core;
[0065] (2) Inject simulated crude oil into the core at a constant flow rate to measure the oil phase permeability K at bound water saturation 油1 ;
[0066] (3) Inject simulated brine into the core at a constant flow rate to measure the water permeability K at residual oil saturation 水1 ;
[0067] (4) Inject 1PV of oil-stabilizing and water-controlling agent system into the same core in reverse order and keep it at a constant temperature in a thermostat for 24 h;
[0068] (5) Inject simulated brine into the core at a constant flow rate until the pressure and flow rate are constant, and measure the water phase permeability K 水2 ;
[0069] (6) Inject simulated crude oil into the core at a constant flow rate until the pressure and flow rate are constant, and measure the oil phase permeability K 油2 ;
[0070] (7) Calculate the oil phase and water phase permeability reduction rate N before and after injection of the oil stabilization and water control system 油0 and N 水0 , and calculate the ratio of the water phase permeability reduction rate to the oil phase permeability reduction rate (denoted as M0);
[0071] (8) Inject simulated brine into the core multiple times at a constant flow rate, with a single injection volume of 20 PV;
[0072] (9) After a single injection of simulated brine, simulated crude oil is injected into the core at a constant flow rate to measure the oil phase permeability K at the irreducible water saturation after the cumulative injection of simulated brine in step (8) 油nn (n=20, 60, 80, 100);
[0073] (10) Injecting simulated brine into the core at a constant flow rate, and measuring the water phase permeability K at the residual oil saturation after the cumulative injection of simulated brine in step (8) 水n (n=20, 60, 80, 100);
[0074] (11) Calculate the oil and water permeability reduction rate N after injecting the oil stabilization and water control system and water injection flushing n PV (n = 20, 60, 80, 100) and before injecting the oil stabilization and water control system. 油n (n=20, 60, 80, 100) and N 水n (n = 20, 60, 80, 100), and calculate the ratio of the water phase permeability reduction rate to the oil phase permeability reduction rate after water injection and flushing n PV, recorded as M n (n=20, 60, 80, 100);
[0075]
[0076] The ratio of the water phase permeability reduction rate to the oil phase permeability reduction rate, M0, is used as an evaluation index for the effect of stabilizing oil and controlling water.n As a long-term indicator; the larger the M0, the better the oil stabilization and water control effect. n The bigger it is, the better the long-term effect.
[0077] Example 1: Preparation of permeability improver A—AM / octadecyl dimethyl allyl ammonium chloride / methacryloyloxyethyl trimethyl ammonium chloride / AMPS / NaAA copolymer
[0078] (1) Weigh 739.42 g of deionized water into a 1 L beaker, add 250 g of acrylamide AM and 37.5 g of 2-acrylamido-2-methylpropanesulfonic acid AMPS (15 wt.% of acrylamide AM), stir evenly, and add 7.25 g of sodium hydroxide to adjust the pH value to 7.0;
[0079] (2) Add 18.75 g of octadecyl dimethyl allyl ammonium chloride (7.5 wt.% of the amount of acrylamide AM) and 5.0 g of methacryloyloxyethyl trimethyl ammonium chloride (2 wt.% of the amount of acrylamide AM) and fully dissolve;
[0080] (3) The polymerization system was heated to 30° C., 3.13 g of 20% ammonium persulfate solution and 5.0 g of 20% sodium bisulfite solution were added to initiate polymerization, and adiabatic polymerization was performed for 8 h;
[0081] (4) After the adiabatic polymerization, the colloid was taken out and cut into particles of 2-4 mm, and a hydrolyzing agent sodium hydroxide (2.64 g sodium hydroxide / 100 g colloid particles, i.e., the ratio of NaAA was 20%) was added according to the theoretical hydrolysis degree of 20% and hydrolyzed at 100° C. for 3 h;
[0082] (5) After the hydrolysis is completed, the product is dried at 100°C for 1 hour and crushed and sieved to obtain a 100-120 mesh phase penetration improver A with a molecular weight of 2.2552 million.
[0083] Example 2: Preparation of Phase Penetration Improver A-1—AM / Octadecyldimethylallylammonium chloride / Methacryloyloxyethyltrimethylammonium chloride / AMPS / NaAA Copolymer
[0084] (1) Weigh 739.42 g of deionized water into a 1 L beaker, add 250 g of acrylamide AM and 50.0 g of 2-acrylamido-2-methylpropanesulfonic acid AMPS (20 wt.% of acrylamide AM), stir evenly, and add 9.66 g of sodium hydroxide to adjust the pH value to 7.0;
[0085] (2) Add 25 g of octadecyl dimethyl allyl ammonium chloride (10 wt.% of the amount of acrylamide AM) and 7.5 g of methacryloyloxyethyl trimethyl ammonium chloride (3 wt.% of the amount of acrylamide AM) and fully dissolve;
[0086] (3) The polymerization system was heated to 30° C., 3.13 g of 20% ammonium persulfate solution and 5.0 g of 20% sodium bisulfite solution were added to initiate polymerization, and adiabatic polymerization was performed for 8 h;
[0087] (4) After the adiabatic polymerization, the colloid was taken out and cut into particles of 2-4 mm, and a hydrolyzing agent sodium hydroxide (4.62 g sodium hydroxide / 100 g colloid particles, i.e., the ratio of NaAA was 35%) was added according to the theoretical hydrolysis degree of 35% and hydrolyzed at 100° C. for 3 h;
[0088] (5) After the hydrolysis was completed, the product was dried at 100°C for 1 hour and crushed and sieved to obtain a 100-120 mesh permeability improver A-1 with a molecular weight of 1.8094 million.
[0089] Example 3: Preparation of permeability improver A-2—AM / octadecyl dimethyl allyl ammonium chloride / methacryloyloxyethyl trimethyl ammonium chloride / AMPS / NaAA copolymer
[0090] (1) Weigh 739.42 g of deionized water into a 1 L beaker, add 250 g of acrylamide AM and 25.0 g of 2-acrylamido-2-methylpropanesulfonic acid AMPS (10 wt.% of acrylamide AM), stir evenly, and add 4.83 g of sodium hydroxide to adjust the pH value to 7.0;
[0091] (2) Add 12.5 g of octadecyl dimethyl allyl ammonium chloride (5 wt.% of the amount of acrylamide AM) and 2.5 g of methacryloyloxyethyl trimethyl ammonium chloride (1 wt.% of the amount of acrylamide AM) and fully dissolve;
[0092] (3) The polymerization system was heated to 30° C., 3.13 g of 20% ammonium persulfate solution and 5.0 g of 20% sodium bisulfite solution were added to initiate polymerization, and adiabatic polymerization was performed for 8 h;
[0093] (4) After the adiabatic polymerization, the colloid was taken out and cut into particles of 2-4 mm, and sodium hydroxide (1.98 g sodium hydroxide / 100 g colloid particles, i.e., the ratio of NaAA was 15%) was added according to the theoretical hydrolysis degree of 15% and hydrolyzed at 100° C. for 3 h;
[0094] (5) After the hydrolysis was completed, the product was dried at 100°C for 1 hour and crushed and sieved to obtain a 100-120 mesh permeability improver A-2 with a molecular weight of 3.8775 million.
[0095] Example 4: Preparation of Phase Penetration Improver A-3—AM / Octadecyldimethylallylammonium chloride / Methacryloyloxyethyltrimethylammonium chloride / AMPS / NaAA Copolymer
[0096] (1) Weigh 739.42 g of deionized water into a 1 L beaker, add 250 g of acrylamide AM and 75 g of 2-acrylamido-2-methylpropanesulfonic acid AMPS (30 wt.% of acrylamide AM), stir evenly, and add 14.49 g of sodium hydroxide to adjust the pH value to 7.0;
[0097] (2) Add 50 g of octadecyl dimethyl allyl ammonium chloride (20 wt.% of the amount of acrylamide AM) and 12.5 g of methacryloyloxyethyl trimethyl ammonium chloride (5 wt.% of the amount of acrylamide AM) and fully dissolve;
[0098] (3) The polymerization system was heated to 30° C., 3.13 g of 20% ammonium persulfate solution and 5.0 g of 20% sodium bisulfite solution were added to initiate polymerization, and adiabatic polymerization was performed for 8 h;
[0099] (4) After the adiabatic polymerization is completed, the colloid is taken out and cut into particles of 2-4 mm, and a hydrolyzing agent sodium hydroxide (6.60 g sodium hydroxide / 100 g colloid particles, i.e., the ratio of NaAA is 50%) is added according to a theoretical hydrolysis degree of 50% and hydrolyzed at 100° C. for 3 h;
[0100] (5) After the hydrolysis was completed, the product was dried at 100°C for 1 hour and crushed and sieved to obtain a 100-120 mesh permeability improver A-3 with a molecular weight of 868,200.
[0101] Example 5: Preparation of Phase Penetration Improver A-4—AM / Octadecyldimethylallylammonium chloride / Methacryloyloxyethyltrimethylammonium chloride / AMPS / NaAA Copolymer
[0102] (1) Weigh 739.42 g of deionized water into a 1 L beaker, add 250 g of acrylamide AM and 12.5 g of 2-acrylamido-2-methylpropanesulfonic acid AMPS (5 wt.% of acrylamide AM), stir evenly, and add 2.42 g of sodium hydroxide to adjust the pH value to 7.0;
[0103] (2) Add 6.25 g of octadecyl dimethyl allyl ammonium chloride (2.5 wt.% of the amount of acrylamide AM) and 1.25 g of methacryloyloxyethyl trimethyl ammonium chloride (0.5 wt.% of the amount of acrylamide AM) and fully dissolve;
[0104] (3) The polymerization system was heated to 30° C., 3.13 g of 20% ammonium persulfate solution and 5.0 g of 20% sodium bisulfite solution were added to initiate polymerization, and adiabatic polymerization was performed for 8 h;
[0105] (4) After the adiabatic polymerization, the colloid was taken out and cut into particles of 2-4 mm, and a hydrolyzing agent sodium hydroxide (0.66 g sodium hydroxide / 100 g colloid particles, i.e., the ratio of NaAA was 5%) was added according to the theoretical hydrolysis degree of 5% and hydrolyzed at 100° C. for 3 h;
[0106] (5) After the hydrolysis was completed, the product was dried at 100°C for 1 h, and then crushed and sieved to obtain a 100-120 mesh permeability improver A-4 with a molecular weight of 4,265,800.
[0107] Example 6: Preparation of permeability improver B—AM / octadecyl dimethyl allyl ammonium chloride / AMPS / NaAA copolymer
[0108] Compared with Example 1, the only difference is that methacryloyloxyethyl trimethyl ammonium chloride is not added, and the amount of octadecyl dimethyl allyl ammonium chloride used is 7.5 wt.% of acrylamide AM;
[0109] The molecular weight of penetration improver B is 2.9735 million.
[0110] Example 7: Preparation of permeability improver C-AM / methacryloyloxyethyl trimethylammonium chloride / AMPS / NaAA copolymer
[0111] Compared with Example 1, the only difference is that octadecyl dimethyl allyl ammonium chloride is not added, and the amount of methacryloyloxyethyl trimethyl ammonium chloride is 2 wt.% of acrylamide AM;
[0112] The molecular weight of penetration improver C is 2.8463 million.
[0113] Example 8: Preparation of permeability improver D—AM / AMPS / NaAA copolymer
[0114] Compared with Example 1, the difference is that octadecyl dimethyl allyl ammonium chloride and methacryloyloxyethyl trimethyl ammonium chloride are not added, and 2.5 g of sodium formate is used instead;
[0115] The molecular weight of the permeability improver D is 3.8748 million.
[0116] Embodiment 9:
[0117] Using water as solvent, 0.04% solution of phase penetration improver AD was prepared respectively, 0.2% by mass of sodium persulfate was added to the solution, and the solution was placed in a 50° C. water bath for sufficient gel breaking for 24 hours to obtain the phase penetration improver AD after gel breaking.
[0118] Example 10: Preparation of a fracturing fluid system containing a phase permeability improver
[0119] Fracturing fluid system formula: 0.4% thickener (water-soluble polyacrylamide with a viscosity-average molecular weight ≥ 25 million), 0.04% AM phase permeability improver (the phase permeability improvers of Examples 1-4 are used respectively, and the obtained fracturing fluid systems are named fracturing fluid systems A, B, C, and D respectively), 0.2% clay stabilizer (potassium chloride), 0.25% drainage aid (perfluorodecyl ether fluorocarbon surfactant FHJ-601, Hebi Huajian Environmental Protection Technology Co., Ltd.), 0.25% demulsifier (polyoxyethylene polyoxypropylene ether demulsifier L35, Hai'an Petrochemical Plant, Jiangsu Province), 0.20% breaker (potassium persulfate);
[0120] Preparation process of fracturing fluid system: 350 mL of water was measured and poured into a 500 mL beaker, and stirred with a vertical constant speed stirrer, and the speed was adjusted to 500 rad / min; a quantitative thickener, AM / octadecyl dimethyl allyl ammonium chloride / methacryloyloxyethyl trimethyl ammonium chloride / AMPS / NaAA copolymer, clay stabilizer (potassium chloride), 0.25% drainage agent (perfluorodecyl ether fluorocarbon surfactant FHJ-601, Hebi Huajian Environmental Protection Technology Co., Ltd.), 0.25% demulsifier (polyoxyethylene polyoxypropylene ether demulsifier L35, Hai'an Petrochemical Plant, Jiangsu Province), and gel breaker (potassium persulfate) were added in sequence according to the formula, and stirring was continued for 1.5 minutes and then stopped to obtain the product;
[0121] Embodiment 11
[0122] The only difference from Example 10 is that no phase permeability improver is added, and the prepared fracturing fluid system is named fracturing fluid system E.
[0123] Example 12: Preparation of a fracturing fluid system containing a post-gel permeability improver
[0124] Compared with Example 10, the only difference is that the phase permeability improver is the phase permeability improver AD obtained in Example 5 after gel breaking, and the obtained fracturing fluid systems are named fracturing fluid systems F, G, H, and I, respectively.
[0125] Test example: Evaluation of oil stabilization and water control effects
[0126] With reference to SY / T5107-2016 "Method for evaluating performance of water-based fracturing fluid", cores with porosity in the range of 23-26% were selected to test the changes in oil-water permeability in the pores of reservoir rocks before and after the injection of the various permeability improvers and pressure systems of the embodiments of the present invention, as well as the oil-water permeability after a certain amount of simulated brine was injected, and the ratio of the water phase permeability reduction rate to the oil phase permeability reduction rate M0 was used as an evaluation index for the stabilization of oil and water control effect, M n(n=20, 60, 80, 100) as the long-term index; wherein, the oil stabilization and water control effects of the phase permeability improvers prepared in Examples 1-8 are shown in Table 1; the oil stabilization and water control effects of the phase permeability improver AD after demulsification in Example 9 are shown in Table 2; the oil stabilization and water control effects of the fracturing fluid system E containing the phase permeability improver AD in Example 10 and not containing the phase permeability improver in Example 11 are shown in Table 3; the oil stabilization and water control effects of the fracturing fluid system containing the phase permeability improver AD after demulsification in Example 12 are shown in Table 4;
[0127] Table 1 The oil stabilization and water control effect of the phase permeability improver
[0128]
[0129] It can be seen from Table 1 that the phase permeability improvers prepared in Examples 1-3 have good oil stabilization and water control effects, among which the phase permeability improver A series has the best oil stabilization and water control effect, the water phase permeability reduction is greater than 90%, the oil phase permeability reduction is less than 10%, and the reduction ratio reaches 10.24. After water injection and flushing of 100PV, the ratio of the reduction of water phase permeability to oil phase permeability reaches 8.03, which has good long-term effectiveness; in Examples 4 and 5, due to the excessive or low dosage of APMS, hydrophobic functional monomers A and B, the reduction of water phase permeability is reduced, and the oil phase permeability is reduced. The amplitude increases; while the copolymers of Examples 6 and 7 containing only one cationic hydrophobic monomer, namely, the permeability improvers B and C, have a water-phase and oil-phase permeability reduction ratio of about 3.0. After 80PV of water injection, the water-phase permeability reduction ratio to the oil-phase permeability reduction ratio is close to 1.0, and the long-term effect is poor; the AM / AMPS / NaAA copolymer prepared in Example 8, namely, the permeability improver D, which does not contain a cationic monomer, has a significantly poor oil stabilization and water control effect, and the water-phase and oil-phase permeability reduction ratio is only 1.37. After 20PV of water injection, the water-phase permeability reduction ratio to the oil-phase permeability reduction ratio is close to 1, and the long-term effect is even worse.
[0130] Table 2 The oil stabilization and water control effect of the phase permeability improver after gel breaking
[0131]
[0132] It can be seen from Table 2 that the phase permeability improver A series prepared in Example 1 still has relatively excellent oil stabilization and water control performance after sufficient gel breaking, and its water phase permeability reduction is greater than 90%, and the oil phase permeability reduction is less than 10%, and the reduction ratio reaches 10.03. After water injection and flushing of 100PV, the water phase permeability and oil phase permeability reduction ratio is 7.69, which has good long-term effectiveness; while the copolymers containing only one cationic hydrophobic monomer and the phase permeability improvers prepared in Examples 6 and 7 The permeability improvement agent B and C has a water-phase and oil-phase permeability reduction ratio of about 2.0 after gel breaking. After 60PV of water injection, the water-phase permeability reduction ratio is close to 1, and the long-term effect is poor. The AM / AMPS / NaAA copolymer prepared in Example 8 without a cationic monomer, i.e., the permeability improvement agent D, has a significantly worse oil stabilization and water control effect. The water-phase and oil-phase permeability reduction ratio is only 1.09. After 20PV of water injection, the water-phase permeability reduction ratio is close to 1, and the long-term effect is even worse.
[0133] Combining Table 1 and Table 2, it can be seen that the oil stabilizing and water controlling effects and scour resistance of the phase permeability improvers prepared in Example 1, Example 2, and Example 3 are basically the same before and after gel breaking; Example 4 and Example 5 have decreased; while the oil stabilizing and water controlling effects of the phase permeability improvers B, C, and D prepared in Example 6, Example 7, and Example 8 are significantly reduced after gel breaking. After water injection and scouring, the ratio of the reduction in water phase permeability to oil phase permeability rapidly approaches 1, and the long-term effectiveness is poor.
[0134] Table 3 Oil stabilization and water control effects of fracturing fluid system AE It can be seen from Table 3 that the fracturing fluid system A containing phase permeability improver A has a reduction of more than 80% in water phase permeability and about 20% in oil phase permeability, with significant water control effect. After water injection and flushing of 100PV, the water phase permeability and oil phase permeability reduction ratio is 3.57, which has good long-term effectiveness. The fracturing fluid systems B and C containing phase permeability improvers B and C have a reduction of less than 50% in water phase permeability and about 30% in oil phase permeability, with poor oil stabilization and water control effect, and after water injection and flushing of 60PV, the water phase permeability and oil phase permeability reduction ratio is close to 1, with poor long-term effectiveness; the fracturing fluid system D containing phase permeability improver D has a reduction of less than 50% in water phase permeability and about 30% in oil phase permeability, with poor oil stabilization and water control effect, and after water injection and flushing of 40PV, the water phase permeability and oil phase permeability reduction ratio is close to 1, with poor long-term effectiveness. The fracturing fluid system E without any phase permeability improver has poor oil stabilization and water control effects and long-term effectiveness.
[0135] Table 4 Oil stabilization and water control effects of fracturing fluid system FI
[0136]
[0137] It can be seen from Table 4 that the fracturing fluid system F containing the post-breakage permeability improver A still has a good effect of stabilizing oil and controlling water, with a reduction rate of more than 80% for the water phase permeability and more than 20% for the oil phase permeability. After 100PV of water injection, the reduction ratio of the water phase permeability to the oil phase permeability is 2.88, which has good long-term effectiveness. The fracturing fluid systems G and H containing the post-breakage permeability improvers B and C have poor effects of stabilizing oil and controlling water. While reducing the water phase permeability, the oil phase permeability is also significantly reduced, and after 60PV of water injection, the reduction ratio of the water phase permeability to the oil phase permeability is close to 1, and the long-term effectiveness is poor. The fracturing fluid system I containing the post-breakage permeability improver D has a poor effect of stabilizing oil and controlling water. While reducing the water phase permeability, the oil phase permeability is also significantly reduced, and after 20PV of water injection, the reduction ratio of the water phase permeability to the oil phase permeability is close to 1, and the long-term effectiveness is even worse.
[0138] Finally, it should be noted that the above content is only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Simple modifications or equivalent substitutions of the technical solution of the present invention by ordinary technicians in this field do not deviate from the essence and scope of the technical solution of the present invention.
Claims
1. A phase penetration improver, characterized in that: The invention is prepared by copolymerizing acrylamide AM, a functional monomer 2-acrylamide-2-methylpropanesulfonic acid AMPS, a cationic hydrophobic monomer A and a cationic hydrophobic monomer B and then hydrolyzing them. Based on acrylamide AM, the amounts of the raw materials are as follows: 10-20 wt.% of the functional monomer 2-acrylamide-2-methylpropanesulfonic acid AMPS, 5-10 wt.% of the cationic hydrophobic monomer A and 1-3 wt.% of the cationic hydrophobic monomer B.
2. The phase penetration improver according to claim 1, characterized in that The cationic hydrophobic monomer A is at least one of tetradecyl dimethyl allyl ammonium chloride, hexadecyl dimethyl allyl ammonium chloride and octadecyl dimethyl allyl ammonium chloride.
3. The phase penetration improver according to claim 1, characterized in that The cationic hydrophobic monomer B is at least one of methacryloyloxyethyl trimethyl ammonium chloride, acryloyloxyethyl trimethyl ammonium chloride and acryloyloxyethyl dimethyl benzyl ammonium chloride.
4. The phase penetration improver according to any one of claims 1 to 3, characterized in that: The particle size of the phase penetration improver is 100-120 meshes, and the viscosity average molecular weight is 500,000-5,000,000.
5. The method for preparing the phase penetration improver according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) Add acrylamide AM and functional monomer 2-acrylamido-2-methylpropanesulfonic acid AMPS into deionized water and adjust the pH value of the solution to 7.0; (2) adding cationic hydrophobic monomer A and cationic hydrophobic monomer B and stirring evenly; (3) raising the temperature, adding an initiator, and performing adiabatic polymerization; (4) After completion, a hydrolysis agent is added to carry out a hydrolysis reaction; (5) Drying to obtain the phase penetration improver.
6. The preparation method according to claim 5, characterized in that: The initiator comprises an oxidant and a reductant; the oxidant is at least one of potassium persulfate, ammonium persulfate, sodium persulfate and dibenzoyl peroxide; the reductant is at least one of sodium formaldehyde sulfoxylate, sodium sulfite, sodium bisulfite and urea.
7. The preparation method according to claim 6, characterized in that: The amount of the oxidizing agent is 0.1-0.4 wt.% of acrylamide AM; the amount of the reducing agent is 0.2-0.6 wt.% of acrylamide AM.
8. The preparation method according to claim 5, characterized in that: The hydrolyzing agent is at least one of sodium hydroxide, sodium carbonate and sodium bicarbonate.
9. The preparation method according to claim 5, characterized in that: The dosage of the hydrolyzing agent is calculated based on a theoretical hydrolysis degree of 15-35%.
10. The preparation method according to claim 5, characterized in that: The polymerization reaction temperature is 30-50°C, and the reaction time is 4-12h; the hydrolysis reaction temperature is 80-120°C, and the hydrolysis reaction time is 1-4h; the drying temperature is 80-140°C, and the drying time is 0.5-3h.
11. A fracturing fluid system, characterized in that: The invention comprises the phase penetration improver described in any one of claims 1 to 4 or the phase penetration improver prepared by the preparation method described in any one of claims 5 to 10.
12. The fracturing fluid system according to claim 11, characterized in that: Calculated by mass percentage, it includes: 0.4-1.2% thickener, 0.1-0.5% clay stabilizer, 0.1-0.5% drainage aid, 0.1-0.5% demulsifier, 0.05-0.20% gel breaker and 0.03-0.05% phase penetration improver.
13. The fracturing fluid system according to claim 12, characterized in that: The thickener is water-soluble polyacrylamide and its derivatives; the clay stabilizer is at least one of potassium chloride, ammonium chloride and quaternary ammonium salt organic clay stabilizers; the drainage agent is a fluorocarbon surfactant, including perfluorodecyl ether fluorocarbon surfactant and / or perfluorodecyl polyoxyethylene ether fluorocarbon surfactant; the demulsifier is a polyether compound, including at least one of polyoxyethylene polyoxypropylene ether demulsifier, polyoxyethylene polyoxypropylene ether demulsifier and polyoxyethylene polyoxypropylene ether demulsifier; the breaker is at least one of ammonium persulfate, sodium persulfate, potassium persulfate and capsule breaker.
14. The fracturing fluid system according to claim 12, characterized in that: The thickener is in the form of an emulsion or a powder of 100-120 meshes.
15. The method for preparing a fracturing fluid system according to any one of claims 11 to 14, characterized in that: Add thickener, phase penetration improver, clay stabilizer, drainage aid, demulsifier and gel breaker into water in sequence and stir to obtain the product.
16. The preparation method according to claim 15, characterized in that: The stirring process has a rotation speed of 400-800 rad / min and a stirring time of 1-3 min.
17. Application of a phase permeability improver or a fracturing fluid system in hydraulic fracturing exploitation in oil and gas fields, characterized in that: The phase permeability improver is the phase permeability improver described in any one of claims 1-4 or the phase permeability improver prepared by the preparation method described in any one of claims 5-10; the fracturing fluid system is the fracturing fluid system described in any one of claims 11-14 or the fracturing fluid system prepared by the preparation method described in any one of claims 15-16.
Citation Information
Patent Citations
Water control agent for oil well and preparation method thereof
CN102093880B
A nano-phase permeation improver for acid fracturing, its preparation method and application
CN111574992B
Selective water-blocking agents and long-lasting oil stabilization and water control methods for oil and gas fields under high temperature and high pressure.
CN113666686B
Fracturing method for improving recovering ratio by phase permeability improver
CN1614193A
Hydrophobic associative polymer gel microsphere profile control agent and preparation method thereof
CN109666097A
Cited By
Relative permeability improver capable of efficiently controlling water and increasing oil and preparation method of relative permeability improver
CN120271749A